2019
DOI: 10.1080/14760584.2019.1562344
|View full text |Cite
|
Sign up to set email alerts
|

Current landscape of nonmedical vaccination exemptions in the United States: impact of policy changes

Abstract: Introduction: In the United States, high childhood vaccination coverage has reduced the morbidity and mortality due to vaccine-preventable diseases. The success of vaccination programs in achieving this high coverage is due, in part, to vaccination mandates for school entry. All states have such mandates, but there is heterogeneity across the states in the allowance of non-medical exemptions (e.g. religious or personal belief exemptions) to these mandates. Areas covered:We examine historical trends in non-medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 67 publications
0
36
0
1
Order By: Relevance
“…5,19 Because many states revised their exemption laws during the study period, we recoded exemption law strengths for each state every year with published exemption law summaries. 1,6 We did not include Mississippi and West Virginia because they did not allow nonmedical exemptions. We also excluded Arizona, which allowed personal belief exemptions only in kindergarten.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…5,19 Because many states revised their exemption laws during the study period, we recoded exemption law strengths for each state every year with published exemption law summaries. 1,6 We did not include Mississippi and West Virginia because they did not allow nonmedical exemptions. We also excluded Arizona, which allowed personal belief exemptions only in kindergarten.…”
Section: Methodsmentioning
confidence: 99%
“…In 2016, California eliminated all nonmedical exemptions. 1 Delamater et al 21 studied the rate of medical exemptions in California before and after the legislative change, finding that medical exemptions decreased in the first year after the change. However, by the second year, medical exemption rates rose, and geographic analyses showed that the areas with rising medical exemption rates coincided with areas that previously had high rates of nonmedical exemptions.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Mevcut aşı politikalarını değiştirmek üzere 2014-2018 arasında ABD'nin 26 eyaletinde toplam 70 yasa tasarısı sunulmuştur. 20 Virginia eyaleti 2015 yılında aşı reddi için kişisel inanç istisnasını kaldırmıştır. Aynı yıl Kaliforniya eyaletinde felsefi ve dinî nedenlerle aşı reddine izin verilmemeye başlanmıştır.…”
Section: Bulgularunclassified